Role of Ultrasound in Complications of Hematopoetic Stem Cell Transplantation. Issue 3 (September 2016) - Chauhan, Anil; Faizi, Nauroze A.; Chen, Yin Jie; Jones, Lisa P.; Garg, Naveen; Bhosale, Priya R.
Abstract : Abstract: Hematopoetic stem cell transplantation (HSCT) is an established therapeutic option for both malignant and nonmalignant indications, whose incidence has continued to increase in recent years. Because of its lower cost and lack of radiation exposure, ultrasound examination is often the first-line imaging modality in evaluating patients both before and after HSCT. It is important for radiologists to be aware of sonographic manifestations of the complications that may arise from HSCT. In this study, we will review the basics of HSCT, the role of imaging, and ultrasound examination findings in common and uncommon complications arising from HSCT.